ANALISIS SIKAP RASIONAL PEDAGANG KECIL DALAM MENOLAK PINJAMAN MODAL DARI RENTERNIR - R. Ery Wibowo Agung Santosa; Setia Budhi Wilardjo (Universitas Muhammadiyah Semarang, 2017)
THE EXISTENCE RENTERNIR UNLAWFUL BECAUSE CONTRARY TO THE banking legislation in force in Indonesia (Law No. 16 of 1998). From the viewpoint of Islam renternir synonymous with usury.Riba is haraam. Borrowing money from renternir for business purposes may increase the risk of law and of the cost of capital is very expensive because of higher interest rates.The main objective of this study was to analyze the impact of usury understanding, spiritual guidance, and understanding of Islamic banks on the attitudes of small traders in avoiding capital loan of renternir. The results of this study found evidence that the attitude of traders to reject capital financing from a loan shark is a rational choice. This is consistent with the theory that human agency is assumed to act rationally in accordance with economic motives (M Jensen and W. Meckling, 1976). Neo-classical theory states that rational action leads to material benefits or utility (Etzioni, 1986 and 1988). But the interesting thing in this study is the attitude of small traders are not affected by the understanding of Islamic banks. Keywords: Islamic banks, spiritual guidance, usury, attitude